The Use of Natural Sciences Kits in Distance Learning for Higher Education of Bachelor of Elementary School Teacher Education Program: The Use of Natural Sciences Kits in Distance Learning for Higher Education of Bachelor of Elementary School Teacher Education Program - Budiastra, A.A. Ketut; Kusmawan, Udan; Wicaksono, Iwan; Kartimi (Advances in Social Sciences Research Journal, 2020)
The teaching and learning process of natural science cannot be separated from practicum activities. Likewise, the practicum activities of natural science in bachelor of Elementary School Teacher Education Program have their own characteristics. This study aims at examining the use of Natural Science Kits in the implementation of the practicum of natural sciences with the provisions contained in the practicum of natural sciences college subject of bachelor of Elementary School Teacher Education Program, Faculty of Teacher Training and Education, Universitas Terbuka. This study is categorized as a qualitative descriptive research. This study involved 177 undergraduate students of bachelor of Elementary School Teacher Education Program, UT, which is spread across five (5) regional offices of UT, and it conducted from March to December 2018. The results of this study showed that it can be concluded that the practicum of natural science in elementary schools can be carried out using the Natural Science Kits belonging to bachelor of Elementary School Teacher Education Program, UT, although the Natural Science Kits and its management activities still needs to be improved and refined.